2018
DOI: 10.18805/ijare.a-4876
|View full text |Cite
|
Sign up to set email alerts
|

Status of available sulphur and cationic micronutrients in cultivated soils of Banaskantha district of Gujarat

Abstract: In order to assess the available sulphur and micronutrients (Fe, Mn, Zn and Cu)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…This might be due to facts that with increase in organic matter in soil, the clay-humus complex become more active thereby providing more exchangeable sites and access to sulphur. These results are in same lines to those of Dipali Desai et al, (2018) and Rajput et al (2015).…”
Section: Available Phosphorussupporting
confidence: 90%
“…This might be due to facts that with increase in organic matter in soil, the clay-humus complex become more active thereby providing more exchangeable sites and access to sulphur. These results are in same lines to those of Dipali Desai et al, (2018) and Rajput et al (2015).…”
Section: Available Phosphorussupporting
confidence: 90%
“…
use of organic manure and restricted recycling of crop residues (Prasad, 1999). On the basis of 7587 soil samples collected from different districts of Gujarat, it was found that 25.9 and 25.6 per cent samples were deficient in Fe and Zn, respectively (Patel et al, 2018). Desai et al, (2018) collected 556 soil samples from different talukas of Banaskantha district and found that 34.8 and 37.6 per cent samples
…”
mentioning
confidence: 99%